Allostatic hypermetabolic response in PGC1α/β heterozygote mouse despite mitochondrial defects. Issue 9 (9th August 2021) - Rodriguez‐Cuenca, Sergio; Lelliot, Christopher J.; Campbell, Mark; Peddinti, Gopal; Martinez‐Uña, Maite; Ingvorsen, Camilla; Dias, Ana Rita; Relat, Joana; Mora, Silvia; Hyötyläinen, Tuulia; Zorzano, Antonio; Orešič, Matej; et al.
Abstract: Aging, obesity, and insulin resistance are associated with low levels of PGC1α and PGC1β coactivators and defective mitochondrial function. We studied mice deficient for PGC1α and PGC1β [double heterozygous (DH)] to investigate their combined pathogenic contribution. Contrary to our hypothesis, DH mice were leaner, had increased energy dissipation, a pro‐thermogenic profile in BAT and WAT, and improved carbohydrate metabolism compared to wild types. WAT showed upregulation of mitochondriogenesis/oxphos machinery upon allelic compensation of PGC1α4 from the remaining allele. However, DH mice had decreased mitochondrial OXPHOS and biogenesis transcriptomes in mitochondria‐rich organs. Despite being metabolically healthy, mitochondrial defects in DH mice impaired muscle fiber remodeling and caused qualitative changes in the hepatic lipidome. Our data evidence first the existence of organ‐specific compensatory allostatic mechanisms are robust enough to drive an unexpected phenotype. Second, optimization of adipose tissue bioenergetics is sufficient to maintain a healthy metabolic phenotype despite a broad severe mitochondrial dysfunction in other relevant metabolic organs. Third, the decrease in PGC1s in adipose tissue of obese and diabetic patients is in contrast with the robustness of the compensatory upregulation in the adipose of the DH mice.